Design strategies for the development of a Pd-based acetylene hydrochlorination catalyst: improvement of catalyst stability by nitrogen-containing ligands. Issue 37 (11th July 2019) - He, Haihua; Zhao, Jia; Wang, Bolin; Yue, Yuxue; Sheng, Gangfeng; Wang, Qingtao; Yu, Lu; Hu, Zhong-Ting; Li, Xiaonian
Abstract : The activation of substrates over Pd active sites and the corresponding dispersion could be enhanced by the introduction of N-containing ligands. Abstract : Acetylene hydrochlorination is an attractive chemical reaction for the manufacture of polyvinyl chloride (PVC), and the development efforts are focused on the search for non-mercury catalyst systems. Supported Pd-based catalysts have relatively high activity in the catalytic hydrochlorination of acetylene but are still deactivated rather quickly. Herein, we demonstrated that the atomically dispersed (NH4 )2 PdCl4 complex, distributed on activated carbon, enabled the highly active and stable production of the vinyl chloride monomer (VCM) through acetylene hydrochlorination under low temperature conditions. We found that the presence of nitrogen-containing ligands in the structure of the active center could remarkably improve the stability of the Pd-based catalysts when compared with the case of the conventional PdCl2 catalyst. Further analyses via X-ray diffraction (XRD), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS) and temperature-programmed reduction (TPR) show that the variations in the Pd dispersion, chemical state and reduction property are caused by the nitrogen-containing ligands. Temperature-programmed desorption (TPD) characterizations illustrated that the N-containing ligands over the (NH4 )2 PdCl4 /AC catalyst might enhance the adsorption of HCl. These findings suggest that in addition to strategies that target the doping modification of support materials, optimization of the structure of the active center complexes provides a new path for the design of highly active and stable Pd-based catalysts.